ANALISA KETERKAITAN PENGELUARAN PEMERINTAH, PENDAPATAN NASIONAL, SUKU BUNGA DAN INVESTASI DI INDONESIA: PENDEKATAN VECTOR ERROR CORRECTION MECHANISM (VECM) - Kansiro, Bahrian; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Investment is an important component to support strong and sustainable economic growth. However, the contribution of investment to economic growth in Indonesia in recent years is still very low when compared to the contribution which given of private consumption component. Factors affecting investment in a country such as national income and interest rates level. In addition, government spending is also believed to have an influence on investment. Neo Classical views that an increase in government spending will lead to a decrease in investment, Keynesian thought otherwise while Ricardian approach assumes that government spending has no effect on investment. This study used Indonesian's economy data series from 1981 to 2011 and Vector Error Correction Mechanism (VECM) to determine the relationship among government spending, national income, interest rates and investments in Indonesia within the period and view short-term and long-term relationships among variables. Empirical results indicate that in the short-term, government expenditure and real interest rate has no effect, while national income has positive and significant effect on investment in Indonesia. On theÂ long-term, government expenditure and interest rates has a significant and negative effect, while the national income has significant and positive effect on investment. Keywords: Investment, Government Expenditures, National Income, Interest Rate, VECM